Chichibabin and IsoChichibabin Pyridinium Syntheses of Isodesmosine, Desmosine, and their Derivatives. Issue 43 (24th October 2018) - Tanaka, Nao; Kurita, Manami; Murakami, Yuko; Usuki, Toyonobu
Abstract : Isodesmosine and desmosine are 1, 2, 3, 5‐tetrasubstituted and 1, 3, 4, 5‐tetrasubstituted pyridinium amino acids that crosslink elastin and exist naturally in a 1:1 ratio. In this work, starting from the corresponding aldehyde and amine, we achieved the selective Chichibabin pyridinium syntheses of isodesmosine and desmosine with protecting groups using 50 mol‐% Pr(OTf)3 in H2 O/DMF (2:1) and H2 O/CH2 Cl2 (1:6), respectively. It is important to note that selective desmosine synthesis (herein called isoChichibabin pyridinium synthesis) has been discovered and reported for the first time. Meanwhile, the reaction of aldehyde and amine bearing one alanine using the same conditions as above afforded the protected isodesmosine‐(Ala)4 and desmosine‐(Ala)4 with no selectivity, suggesting that these reactions imitated the formation of the elastin crosslinkers in nature. Abstract : Selective Chichibabin/isoChichibabin pyridinium syntheses of isodesmosine and desmosine with protecting groups using 50 mol‐% Pr(OTf)3 in H2 O/DMF (2:1) and H2 O/CH2 Cl2 (1:6) were achieved, The reaction of aldehyde and amine bearing one alanine afforded the protected isodesmosine‐(Ala)4 and desmosine‐(Ala)4 with no selectivity.